Abfrações associadas com casos de erosões e abrasões dentárias - Aquino, Alexandre Adolfo de [UNESP] (2013)
Dental erosion is a common affliction amongst people. Its comprehension is very complex, because it ends up being a problem with many factors leading to its development. Some of the causes of this condition are: continuous ingestion of acid beverages or food, medicines, acid ambiences or gastrointestinal problems, alongside physical problems such as malocclusions. Another problem is frequently associated with dental erosion: dental abfraction. The loss of dental structure on cervical areas of the teeth has, for a long time, been considered the cause of both problems. Now a days its known that dental erosion, ingestion of acid foods, malocclusion, are only supporting factors of the real reason of dental abfraction: the excess of loads on dental cusps and occlusal surfaces. Based on a literary review and a clinical case, we will discuss the solution of the aforemented problems